Analisis Pengaruh Manajemen Strategi dan Kepemimpinan pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia - Enaz Olyna Sijabat; Ronnie Resdianto Masman (Journal of Management and Bussines (JOMB), 2024)
This research aims to examine the influence of strategic management and leadership on manufacturing companies listed on the Indonesia Stock Exchange (BEI). The main focus of the research is on managerial and financial restructuring and the impact of Going Concern Audit Opinions as indicators of bankruptcy risk. This research aims to provide an in-depth understanding of risk mitigation efforts and company strategies in facing difficult financial conditions. This research uses a qualitative descriptive approach referring to qualitative research methods. Secondary data was obtained from manufacturing industry financial reports published on the IDX for the period 2015 to 2018 and October 2023. The research sample consisted of 14 manufacturing companies that experienced losses for two consecutive years and received a Going Concern Audit Opinion. This research shows that the Going Concern Audit Opinion can be used as a notification to the company to carry out restructuring, both managerial and financial. Companies that are aware of this risk tend to make changes in managerial structure and strategy, reduce the risk of bankruptcy, and optimize share prices. The COVID-19 pandemic has had a significant impact, accelerating changes in management strategies and emphasizing the importance of adaptation in conditions of uncertainty. The conclusion is that the Going Concern Audit Opinion can be used as a notification to the company to carry out restructuring. Collaborative non-financial and financial restructuring can reduce the risk of bankruptcy, with managerial changes as best practice in mitigating bankruptcy. The company's ability to adapt to change, especially during the pandemic, is the key to future success. Keywords: Leadership, Strategic Management, Going Concern Audit Opinion, Restructuring